Analisis Relasi Pertemanan melalui Perilaku Asertif pada Mahasiswa IAIN Parepare - Fitriani Nengsi; Nur Afiah (Institut Agama Islam Negeri Parepare, 2022)
This research aims to find out how to build friendship relationships through assertive behavior. As well as the positive and negative impacts of friendship relationships built through assertive behavior. The research subjects were IAIN Parepare students. The type of research is qualitative descriptive research. The data collection techniques used were observation, interviews and documentation. The data analysis technique is using qualitative data analysis. The results of this research show that efforts to build friendships through assertive behavior can be done by: students paying more attention to the person they are talking to so they know more about the meaning they want to convey, students must have a sense of empathy, especially when a friend faces a problem, a student shows the right action to fellow group members. The positive impact is encouraging new discoveries in terms of helping each other with college assignments, promoting an attitude of mutual assistance. Meanwhile, the negative impact of friendship relations is excessive solidarity in a group, the formation of various groups based on classmates, school friends or residence and triggering conflicts between students when one member of the group has problems with other people or members of other groups.